Customer Experience and Customer Satisfaction on Blibli Customer Loyalty in the City of Surabaya - Prima Luhur Pambudi; Nuruni Ika Kusuma Wardhani; Zawawi (International Journal of Economics (IJEC), 2023)
The development of the digital world is currently very rapid, progress in the online world every year cannot be doubted. One of the sectors that has been affected by this progress is digital business, namely e-commerce or electronic commerc. eThe user's text is too brief to be rewritten academically. The main aim of this study was to investigate the influence of customer experience and customer satisfaction on customer loyalty, specifically focusing on the Blibli.com platform in the urban context of Surabaya. The present study employed a quantitative methodology, utilizing a purposive sample technique. The research population is loyal customers from Blibli in the city of Surabaya. The sample in this study are customers aged 26-35 years who live in the city of Surabaya, customers who have made purchases at Blibli with a minimum of 2 purchases, and customers who have used the Blibli application for at least 1 year. While the sample in this study were 112 Blibli customer respondents according to the criteria. All tests using the SmartPLS Application show that all tests get scores above the required values so that the tests are declared reliable. The findings of the research indicate that customer experience exerts a substantial and favorable impact on customer loyalty. Similarly, the variable of customer satisfaction exhibits a noteworthy and favorable impact on customer loyalty.